SOLUTION: 3x/x-1 + 6x-9/x-1 -6 = 0

Algebra ->  Algebra  -> Test -> SOLUTION: 3x/x-1 + 6x-9/x-1 -6 = 0       Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Test Calculators and Practice Answers archive Word Problems Lessons In Depth

 Question 150785: 3x/x-1 + 6x-9/x-1 -6 = 0 Answer by mangopeeler07(462)   (Show Source): You can put this solution on YOUR website!Common denominator=x-1 3x/x-1 + 6x-9/x-1 -6 = 0 becomes 3x/x-1 + 6x-9/x-1 -6(x-1)/x-1=0 Distribute the -6 3x/x-1 + 6x-9/x-1 -6x+6/x-1=0 Combine the numerators 3x+6x-9-6x+6/x-1=0 Combine like terms in the numerator 3x-3/x-1=0 0 over anything is zero, so the numerator must be equal to zero. Eliminate the denominator. 3x-3=0 3x=3 x=1 Notice if you plug this back into the original equation, or any of the ones before you eliminated the denominator, the denominator becomes 0. That's undefined. So there is no solution.